Cardiac resynchronization therapy guided by the new KODEX‐EPD imaging system. Issue 5 (30th August 2021) - Scarà, Antonio; Sciarra, Luigi; Bressi, Edoardo; De Ruvo, Ermenegildo; Grieco, Domenico; Borrelli, Alessio; Zecchi, Paolo; Calò, Leonardo
Abstract: Nowadays, fluoroscopy is the standard tool used to help physicians during pacing lead implantation. However, its use entails significant radiation exposure for physicians and especially for patients. For the first time, the present case report describes the use of the electro‐anatomical mapping (EAM) navigation system KODEX‐EPD for cardiac resynchronization therapy (CRT) implantation. These findings suggest that CRT implantation guided by the KODEX‐EPD system is feasible and safe with the minimization of X‐ray and dye exposure. Abstract : CRT‐D electroanatomic mapping system.